Adult female patient with osteitis pubis and pelvic instability requiring surgery: A case report. (December 2020) - Nasrallah, Khalil; Jammal, Mahmoud; Khoury, Amal; Liebergall, Meir
Abstract: Background: Osteitis pubis (OP) is an inflammatory condition of the symphysis pubis (SP) characterized by focal pain and local tenderness. Pelvic instability (PI) is commonly associated with this condition. It is still not clear if OP leads to PI or it is PI that leads to OP. The exact cause of osteitis pubis is not yet known, although several predisposing factors have been suggested to contribute to this condition. In most cases, it is self-remitting and rarely needs surgical intervention. Case presentation: A 63-year old woman presented with a 12-month history of persistent pain at the symphysis pubis and non-responsive to analgesics. The pain was aggravated by physical activity such as standing and walking. Physical examination showed focal tenderness at the symphysis pubis with no tenderness over the sacroiliac joints or lumbar region. The diagnosis was confirmed by characteristic findings on radiographs, CT and MRI. Surgery was considered after all conservative measures failed. The patient underwent a wedge-shaped resection of the symphysis pubis; the bone defect was filled autologous tri-cortical bone and fixed with dual plating. The outcome was satisfactory with radiologic union and symptom resolution postoperatively. Conclusions: Osteitis pubis due to pelvic instability can cause chronic and persistent pain. In cases where conservative treatment fails, surgery should be considered. We recommend wide surgical resection of all non-viable bone at the symphysis pubis with the addition of tri-cortical iliac bone graft. Double plating should be considered in order to maximize the rate of fusion and further stabilize the fixation.